Sex-related differences in response to masseteric injections of glutamate and nerve growth factor in healthy human participants - Abdelrahman M. Alhilou; Akiko Shimada; Camilla I. Svensson; Peter Svensson; Malin Ernberg; Brian E. Cairns; Nikolaos Christidis (Scientific Reports, 2021)
Abstract The neurophysiological mechanisms underlying NGF-induced masseter muscle sensitization and sex-related differences in its effect are not well understood in humans. Therefore, this longitudinal cohort study aimed to investigate the effect of NGF injection on the density and expression of substance P, NMDA-receptors and NGF by the nerve fibers in the human masseter muscle, to correlate expression with pain characteristics, and to determine any possible sex-related differences in these effects of NGF. The magnitude of NGF-induced mechanical sensitization and pain during oral function was significantly greater in women than in men (P < 0.050). Significant positive correlations were found between nerve fiber expression of NMDA-receptors and peak pain intensity (rs = 0.620, P = 0.048), and expression of NMDA-receptors by putative nociceptors and change in temporal summation pain after glutamate injection (rs = 0.561, P = 0.003). In women, there was a significant inverse relationship between the degree of NGF-induced mechanical sensitization and the change in nerve fiber expression of NMDA-receptors alone (rs = − 0.659, P = 0.013), and in combination with NGF (rs = − 0.764, P = 0.001). In conclusion, women displayed a greater magnitude of NGF-induced mechanical sensitization that also was associated with nerve fibers expression of NMDA-receptors, when compared to men. The present findings suggest that, in women, increased peripheral NMDA-receptor expression could be associated with masseter muscle pain sensitivity.